Integrating sensors for dissolved gas concentrations (CO2 and CH4) into modern measuring platforms - Fietzek, Peer; Kramer, S.; Esser, D. (2011)
Carbon dioxide (CO2) and methane (CH4) concentrations in the oceans are key parameters for addressing many scientific questions as well as industrial applications. Extensive greenhouse gas datasets are important for reliable climate modeling. “Point measurements” help to understand the underlying processes or form the basis for countermeasures. Ocean acidification, natural gas seepage, carbon capture and storage (CCS) as well as pipeline monitoring are only some examples for fields of applications. The need for extended in situ measurements of dissolved CO2 or CH4 can only be met by having the right instrumentation combined with and efficiently integrated into modern platforms. Therefore the sensors need to be small, reliable and intelligent. The demands on sensors and platforms recently follow the same trend of becoming more and more autonomous. Thus it is very important to emphasize the point of sensor integration into platforms at an early stage in order to achieve an intelligent combination of the measuring device and its carrier. The concrete orientation of sensor improvements and developments to the platform manufacturer’s as well as scientific and industrial end-user’s needs leads to an effective, applied and hence successful integration. Sensors of the HydroC family for dissolved CO2 and CH4 determine gas concentrations in a membrane equilibrated headspace using non-dispersive IR-spectrometry. The small size and fast response time of the sensors lead to the deployment on different well-established as well as modern platforms such as buoys, remotely operated and autonomous underwater vehicles (ROVs, AUVs). From November 2010 until today a profiling float being equipped with a HydroC/CO2 as part of its sensor suite (CTD, dissolved oxygen) records an unique dataset. The sensors are continuously improved to e.g. further reduce their power requirements and size. By that even more challenging platforms such as gliders should be accessed.